Involvement of mek signalling on endothelial-like differentiation of dental stem cells cultured on human amniotic membrane with VEGF treatment - Yusof, Muhammad Fuad Hilmi (2021)
Wound healing continues to be a healthcare burden associated with increased morbidity and substantial mortality. Tissue engineering offers a potential solution to address this unmet medical need by building a construct combining cells, growth factor, and scaffold for angiogenesis, a fundamental process for tissue regeneration. A detailed understanding of the molecular mechanism underlying the angiogenic differentiation is vital for developing an engineered tissue for wound healing application. Therefore, this study aimed to investigate the role of the MEK signalling pathway onto the differentiation of stem cells from human exfoliated deciduous teeth (SHED) and VEGF pre-induced SHED into endothelial-like cells when induced with VEGF and cultured on the stromal side (SS) of human amniotic membrane (AM). In order to decipher the pathway involved, the current study was conducted by employing techniques such as flow cytometry, reverse transcription-polymerase chain reaction (RT-PCR), real-time reverse transcription-polymerase chain reaction (qRT-PCR), enzyme-linked immunosorbent assay (ELISA) and immunocytochemistry (ICC). Flow cytochemistry results showed that SHED at passage 10 and 15 positively expressed CD90, CD73, and CD105 mesenchymal stem cell protein markers, indicating that SHED were able to maintain their stemness property. Concurrently, SHED did not express hematopoietic cell markers, namely, CD34, CD11b, CD19, CD45, and HLA-DR. Western blot results showed that Ang-1 and COX-2 endothelial cells protein markers were expressed in differentiated SHED cultured on SS of AM with VEGF treatment on day 1 and 7. RT-PCR findings revealed that differentiated SHED expressed both stem cells (Nestin, Nanog, and CD73) and endothelial-specific markers (Ang-1, COX-2, and VE-Cadherin) in all treatments on day 1, 7, 10, and 14. Twenty four hours VEGF pre-induction elevated the expression of CD73, Nanog, and COX-2. A sub-lethal dose of 1.0 μM MEK inhibitor PD184352 reduced the cell viability significantly (independent sample t-test p<0.05). Statistical analysis using one-way ANOVA for qRT-PCR outcomes demonstrated that VEGF pre-induction upregulated the gene expression of NOS3 and IL-8 significantly at day 1 and 10 (p<0.05). On the other hand, the expression of CD31, vWF, IL1-β, TNF-⍺, E-selectin, ICAM-1, and RCAN -1.4 were not promoted by the pre-induction. MEK inhibitor PD184352 blocked the gene expression of CD31 and NOS3 on day 1 and 7, and the genes were detected on day 10 afterwards. Meanwhile, PD184352 downregulated vWF, IL1-β, and IL-8. In contrast, PD184352 promoted TNF-⍺, E-selectin, ICAM-1, and RCAN-1.4 gene expressions. ELISA results showed that p-ERK, CD31, and MEKK1 protein expression provided confirmatory evidence that VEGF signalling through the MEK/ERK pathway was required for angiogenic differentiation by this proposed construct. Besides, the ICC results of CD31, vWF, and F-actin protein expression enforced that SHED performed endothelial-like differentiation, and it was regulated by MEK signalling. Hence, these findings proposed that the MEK pathway regulates the differentiation of SHED into endothelial-like cells using the proposed construct for wound healing tissue engineering.